Rates of climatic niche evolution are correlated with species richness in a large and ecologically diverse radiation of songbirds. (23rd March 2015) - Title, Pascal O.; Burns, Kevin J.; Mooers, Arne
Abstract By employing a recently inferred phylogeny and museum occurrence records, we examine the relationship of ecological niche evolution to diversification in the largest family of songbirds, the tanagers (Thraupidae). We test whether differences in species numbers in the major clades of tanagers can be explained by differences in rate of climatic niche evolution. We develop a methodological pipeline to process and filter occurrence records. We find that, of the ecological variables examined, clade richness is higher in clades with higher climatic niche rate, and that this rate is also greater for clades that occupy a greater extent of climatic space. Additionally, we find that more speciose clades contain species with narrower niche breadths, suggesting that clades in which species are more successful at diversifying across climatic gradients have greater potential for speciation or are more buffered from the risk of extinction.